2016
DOI: 10.3390/w8030082
|View full text |Cite
|
Sign up to set email alerts
|

Computing Economies of Scope Using Robust Partial Frontier Nonparametric Methods

Abstract: This paper proposes a methodology to examine economies of scope using the recent order-α nonparametric method. It allows us to investigate economies of scope by comparing the efficient order-α frontiers of firms that produce two or more goods with the efficient order-α frontiers of firms that produce only one good. To accomplish this, and because the order-α frontiers are irregular, we suggest to linearize them by the DEA estimator. The proposed methodology uses partial frontier nonparametric methods that are … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 41 publications
(48 reference statements)
0
4
0
Order By: Relevance
“…Moreover, other studies by De Witte and Marques [ 45 ] found no evidence of economies of scope between water and sewerage services in the Portuguese water industry using non-parametric techniques. In contrast, other studies by Carvalho and Marques [ 4 , 6 , 9 , 10 ] found economies of scope in the joint supply of drinking water and wastewater services in Portugal using partial or Bayesian frontier parametric techniques. Sauer [ 52 ] also found no evidence of scope economies between water and sewerage services in Germany using a McFadden variable cost function.…”
Section: Resultsmentioning
confidence: 79%
See 2 more Smart Citations
“…Moreover, other studies by De Witte and Marques [ 45 ] found no evidence of economies of scope between water and sewerage services in the Portuguese water industry using non-parametric techniques. In contrast, other studies by Carvalho and Marques [ 4 , 6 , 9 , 10 ] found economies of scope in the joint supply of drinking water and wastewater services in Portugal using partial or Bayesian frontier parametric techniques. Sauer [ 52 ] also found no evidence of scope economies between water and sewerage services in Germany using a McFadden variable cost function.…”
Section: Resultsmentioning
confidence: 79%
“…Moreover, while several studies have used a translog cost specification to estimate productivity change in water industry [ 18 , 31 ], to the best of our knowledge, the quadratic cost function to estimate the productivity change on the water sector has been hardly researched. Furthermore, as Triebs et al [ 26 ], Molinos-Senante and Maziotis [ 12 , 32 ] noted that there are several advantages for choosing a quadratic cost function over other functional forms such as a translog, composite or generalized composite which have also been used in other studies [ 9 , 10 , 33 , 34 ]. Compared to translog function, a quadratic cost function takes into account zero values.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Cooperation between utilities and customers has the potential for cost and energy savings while balancing the benefits between the participants (provided that the mutual dependence of energy consumption cost among consumers is fairly addressed) [41]. The DNOs, today's de facto electricity providers to the end consumer, are thus required to adjust to new business models that are not necessarily based on volume sales (kWh), but still are expected to remain important players if they consider selling other services such as balancing and security [42].…”
Section: Residential Microgrids Versus Dnosmentioning
confidence: 99%